Dinamika Sosial dan Pengaruhnya Terhadap Transformasi Sosial Masyarakat - Ismunandar, Arif (Tarbawiyah Jurnal Ilmiah Pendidikan, 2019)
Social dynamics are shifts made by the community continuously, causing changes in the life order of the community. While social transformation is a change that occurs not only individuals but includes the entire community. The influence of dynamics on social transformation that occurs in society actually becomes commonplace, because with a meaningful change the direction of development and renewal is ongoing. Maturity in responding to changes and dynamics that occur in the community today can certainly be minimized by the existence of community commitment in decision making and responding to conflicts / events that occur. The structure of community life that has strong characteristics of values, norms, prioritizing deliberation in taking power and diverse cultures is expected to be able to minimize the negative impact of change on society.